AI-generated thinking: are students learning or just completing tasks? - Mohd Shariff, Sazlin Suhalmie; Mohamad, Masilah; Ya'acob, Fatin Farazh (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Artificial intelligence (AI) has undergone rapid evolution in recent years, reshaping not only industries but also the way we approach teaching and learning. Tools such as ChatGPT, Grammarly, and Quillbot have gained popularity among students for their ability to support writing, research, and coding tasks. For some educators, these tools raise serious concerns about academic integrity. For others, they represent valuable aids that can enhance learning and engagement. This growing divide prompts an important question for educators and institutions alike: Should AI tools be banned from student use, or should they be thoughtfully integrated into the future of education? The increasing presence of AI in classrooms presents both challenges and opportunities. While concerns over plagiarism and misuse are legitimate, these tools also offer powerful advantages in personalising support, improving efficiency, developing real-world skills, and promoting inclusivity. Navigating this complex issue requires a balanced perspective that acknowledges the risks without overlooking the benefits.